2021
DOI: 10.1371/journal.pone.0257403
|View full text |Cite
|
Sign up to set email alerts
|

Metformin and sodium dichloroacetate effects on proliferation, apoptosis, and metabolic activity tested alone and in combination in a canine prostate and a bladder cancer cell line

Abstract: An important approach in tumor therapy is combining substances with different action mechanisms aiming to enhance the antineoplastic effect, decrease the therapeutic dosage, and avoid resistance mechanisms. Moreover, evaluating compounds already approved for the treatment of non-neoplastic diseases is promising for new antineoplastic therapies. Sodium dichloroacetate (DCA) reactivates oxidative phosphorylation in the cancer cell mitochondria, reducing apoptosis resistance in cancer cells. Furthermore, metformi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
18
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(19 citation statements)
references
References 84 publications
0
18
0
Order By: Relevance
“…Equal amounts of protein (lysates) or equal volumes (medium) from samples were subjected to SDS-PAGE and immunoblotting (Materials and methods). (A) Trypan blue concentrations more commonly used in studies of an in vitro nature [21][22][23][24]. The future identification of these mechanisms with respect to the effects of DCA on APP proteolysis may lead to the development of novel therapeutics for the treatment of AD.…”
Section: Discussionmentioning
confidence: 99%
“…Equal amounts of protein (lysates) or equal volumes (medium) from samples were subjected to SDS-PAGE and immunoblotting (Materials and methods). (A) Trypan blue concentrations more commonly used in studies of an in vitro nature [21][22][23][24]. The future identification of these mechanisms with respect to the effects of DCA on APP proteolysis may lead to the development of novel therapeutics for the treatment of AD.…”
Section: Discussionmentioning
confidence: 99%
“…In prostate cancer, several studies revealed that metformin mediates reduction in cell viability and arrest at the G1 phase of human prostate cancer cell lines, including DU145, PC3, LNCaP, 22Rv1, C4-2 and also canine prostate cancer cells [49,51,52,[65][66][67][68][69][70][71][72][73][74][75][76][77][78][79][80], without showing evidence of an effect on normal cells (such as RWPE, PREC or P69) [52,66,77]. Due to different experimental designs, some articles did not report metformin to be an apoptotic inducer [65,66,68], and others showed different degrees of apoptotic induction [52,63,[70][71][72][73][77][78][79]81].…”
Section: Prostate Cancermentioning
confidence: 99%
“…Metformin also induced apoptosis after endoplasmic reticulum (ER) stress, promoted by expression of miR-708-5p, which suppresses neuronatin (NNAT), a protein from the endoplasmic reticulum that participates in ER stress [83]. Induction of ROS production is another mechanism involved in metformin-mediated apoptosis [71][72][73].…”
Section: Prostate Cancermentioning
confidence: 99%
See 1 more Smart Citation
“…However, the overall median survival time for dogs that respond to NSAIDs and chemotherapy was still relatively short (up to a few months), which led to the search for novel therapeutic agents. In the past years, multiple studies including canine BC cell lines were conducted in order to evaluate the activity of novel anticancer agents ( Table 3 ) [ 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 ]. Although many of them were not transferred to in vivo studies, novel therapeutic agents that could improve survival of dog pets with bladder TCC were also found.…”
Section: Evidence Synthesismentioning
confidence: 99%